Կովկասի Հայոց Բարեգործական Ընկերության 1894-1902 թթ. գործունեությունը հայ գաղթականության շրջանում - Հակոբյան, Ռուզաննա
Кавказское Армянское Благотворительное Общество было основано в Тбилиси в 1881г., при содействии Б. Навасардяна, Г. Арцруни, Г. Сундукяна и других представителей армянской интеллигенции. В 1894-1896гг. в Турции начались Гамидовские погромы по истреблению армян.Турецкие-армяни спасаясь от погромов, перешла в Закавказье.Там они оказались в тяжелом, безвыходном положении.Общество оказало финансовую и моральную подержку сотни тысячам обездоленным и голодным беженцам.В эти годы общество осуществило активную благотворительную программу, спасая многих беженцев от смерти. Caucasus`s Armenian Charitable Company was established in 1881 in Tbilisi by B.Navasardyan, G.Artsruni,G.Sundukyan and by other armenian intelectuals.From the day of foundation the Company has done many charitable programs.When in 1894-1896, during Hamid`s massacres, the Armenians had to go to Transcaucasia, the Company was in a bad situation.The company started to give material and moral help to a thousands of naked and hungry migrants.The Company implemented vigorous charitable programs during the before-mentioned years, saving many migrants from death.
Keywords: Հայոց պատմություն